Password generation for wireless network with using variable complication rule - Бурячок, Володимир Леонідович; Аносов, Андрій Олександрович; Платоненко, Артем Вадимович (Ukrainian Information Security Research Journal, 2019)
The most dangerous information lately are open Wi-Fi networks. Anyone can connect to them and perform certain malicious actions. Conditionally protected networks in public places or organizations that you can connect to can be considered dangerous, for example, know the password from an employee. One of the causes of cybernetic attacks on the resources of such networks are unsustainable passwords. Their use allows attackers to connect to specified networks and gain access to all devices connected to networks. In addition, if an unstable or standard password is used for the settings panel, then all devices are also at risk of a cyber attack, which can be carried out remotely. The use of an integrated approach by attackers for unauthorized access to wireless communication systems (by combining social engineering and data interception with the use of malware), as well as new types of cyber attacks, which allow to install malicious software on mobile devices can reduce the effectiveness of existing methods and means of protecting wireless networks. In order to avoid such and similar problems, the article proposes a way to increase the protection of wireless networks from intercepting information and influencing it by creating a password that is resistant to selection with a varying complexity rule. This method can be used to create software and hardware security tools, as well as to enhance the protection of user accounts and other security systems where a strong password is required. Considering the statistics and the calculations carried out in the work, it can be argued that the introduction of a method for generating complicated passwords will significantly increase the level of security of wireless networks.